The association between family emotional climate and moral development with vandalism in students: The mediating role of academic self-efficacy - Pakzad Sadeghi; Fatemeh Sadat Marashian; Alireza Heidari (Research and Development in Medical Education)
Background: Research on the mediating role of academic self-efficacy can help identify how the family environment and moral judgment influence destructive behaviors, informing targeted strategies to promote positive youth development. This study investigates the mediating role of academic self-efficacy in the relationship between family emotional climate and moral development with vandalism in students. Methods: In this research, a correlational path analysis framework was adopted to investigate the relationships between various factors and destructive behaviors in adolescents. The target population encompassed all high school students within Eyvan, Iran, during the year 2023. A multistage cluster sampling approach yielded a sample of 364 participants. Standardized instruments assessed vandalism, family emotional climate, moral development, and academic self-efficacy. Structural equation modeling (SEM) software (AMOS 23) was utilized to evaluate the hypothesized model. Results: The findings revealed a non-significant direct association between family emotional climate and vandalism. In contrast, the analysis yielded significant positive and negative associations, respectively, between moral development and academic self-efficacy (P=0.001) and moral development and vandalism (P=0.001). The indirect effect of family emotional climate on vandalism through academic self-efficacy was negative and significant (P=0.012). Similarly, the indirect effect of moral development on vandalism mediated by academic self-efficacy was also negative and significant (P=0.009). Conclusion: These findings highlight the importance of promoting academic self-efficacy alongside efforts to cultivate positive family environments and moral development. By strengthening students’ belief in their academic abilities, interventions can empower them to make positive choices and reduce their likelihood of engaging in destructive behaviors like vandalism.